First International Agribiodiversity Congress in India - Smith, Jimmy W. (International Livestock Research Institute, 2016)
A filmed message by Jimmy Smith, director general of ILRI, to participants at the 1st International Agribiodiversity Congress held 6-9 November 2016 in New Delhi, India.